Estudo Evolutivo da Morfologia e Função Cardíaca em Ratos Submetidos a Estenose Aórtica Supravalvar - Barbosa Ribeiro, Henrique [UNESP]; Okoshi, Katashi [UNESP]; Cicogna, Antonio Carlos [UNESP]; Bregagnollo, Edson Antonio [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Padovani, Carlos Roberto [UNESP]; Aragon, Flávio Ferrari [UNESP]; Jamas, Elenize [UNESP]; Okoshi, Marina Politi [UNESP] (My University, 2003)
Objective - To characterize the follow-up of an experimental model of left ventricular hypertrophy (LVH) induced by supravalvular ascending aortic stenosis in young rats. Methods - Wistar rats were submitted to thoracotomy and aortic stenosis was created by placing a clip on the ascending aorta (AoS group, n = 12). Age-matched control animals underwent a sham operation (C group, n = 12). Cardiac function was analysed by echocardiograms performed 6, 12, and 21 weeks after aortic banding. Myocardial morphological features and myocardial hydroxyproline concentration (HOP) were evaluated 2, 6, 12, and 21 weeks after surgery in additional animals. Results - Aortic banding promoted early concentric LVH and a progressive increase in HOP Under light microscopy, we observed myocyte hypertrophy and wall thickening of the intramural branches of the coronary arteries due to medial hypertrophy. Cardiac function was supranormal after 6 weeks (percentage of fractional shortening - EAo 6: 70.3±10.8; C6: 61.3±5.4; p<0.05), and depressed in the last period. Diastolic dysfunction was detected after 12 weeks (ratio of early-to-late filling velocity - EAo12: 4.20±325; C12: 1.61±0.16; p<0.05). Conclusion - Ascending aortic stenosis promotes concentric LVH with myocardial fibrosis and minimal histological changes. According to the period of evaluation, cardiac function may be improved, normal, or depressed. The model is suitable and useful for studies on pathophysiology and treatment of the different phases of cardiac hypertrophy.
Follow-up Study of Morphology and Cardiac Function in Rats Undergoing Induction of Supravalvular Aortic Stenosis
Keywords: Aortic stenosis and rats; Echocardiogram; Myocardial hypertrophy; Ventricular function